Security superstream : zero trust (O'Reilly Media, Inc., 2022)
With the expansion of the remote workforce, more than ever security professionals need to know exactly who is logging into critical systems and accessing role-appropriate data. Enter zero trust--a network security model based on a strict identity verification process. Join us to get up to speed with key techniques and best practices for the zero-trust model and gain expert advice on emerging guidelines and standards and how to successfully deploy it. You'll learn how to employ multifactor authentication, biometric and behavioral analytics, and continuous monitoring to verify user identities and control access to sensitive resources as you explore the challenges and opportunities of adopting and integrating zero trust into your cybersecurity strategy. What you'll learn and how you can apply it Learn how to view your organization's security and IT infrastructure through the lens of zero trust Understand how zero trust will impact any existing identity, network, and security systems This recording of a live event is for you because... You're a security practitioner interested in implementing zero trust. You're a developer or engineer new to or looking to enter a security role. You want to become well-versed in the foundations and best practices of zero trust. Recommended follow-up: Read: Zero Trust Security: An Enterprise Guide (book) Watch: What Are the Common Challenges to Adopting a Zero Trust Network Security Model? (video).